EMPLOYEE PERFORMANCE MEDIATED THE INFLUENCE OF TALENT MANAGEMENT WITH TRAINING AND DEVELOPMENT ON JOB PROMOTION AT PT PIB - Irwan; Hery Winoto Tj; Eka Desy Purnama (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to determine the influence of talent management as well as training and development on job promotion which is mediated by employee performance. The background for the author to conduct this research is because internal company promotions still have a big opportunity to be improved through a good employee development system, which in the end will create employees with the expected competencies, so that they will be the best candidates to fill the positions needed in the company. later. Using a quantitative approach, this research involved 124 respondents who were PT PIB employees. The questionnaire was created based on indicators of the variables studied. Meanwhile, SmartPLS 4 is an application used in research data analysis techniques. The research results show a t-statistic value of 1.368 for the influence of talent management on job promotions, so talent management has no influence on job promotions. Then the t-statistic value for the influence of training and development on job promotion is 2.437, so training and development has a positive influence on job promotion. The t-statistic value is 2.307 for the influence of talent management on work performance, so talent management has a positive influence on employee performance. Then the t-statistic is 2.927 for the effect of training and development on employee performance, so training and development has a positive influence on employee performance. Employee performance positively mediates the influence of talent management on promotion, with a t-statistic value of 2.121. Furthermore, with a t-statistic value of 2.850, employee performance positively mediates the influence of training and development on job promotion. Employee performance, with a t-statistic value of 7.308, has a positive influence on job promotion, so employee performance has a positive influence on job promotion.